2020
DOI: 10.1038/s41598-020-70387-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and corticosteroids application of different clinical types in patients with corona virus disease 2019

Abstract: To describe the epidemiological and clinical characteristics of patients with Corona Virus Disease 2019 (COVID-19) in Beijing. To analyze the application of corticosteroids in patients with severe pneumonia. We collected information on demographic characteristics, exposure history, clinical characteristics, corticosteroids use, and outcomes of the 65 confirmed cases of COVID-19 at Fifth Medical Center of PLA General Hospital from Jan 20 to Feb 23, 2020. The final follow-up date observed was April 15th, 2020. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…Based on the known and extensive immunosuppressive effects of glucocorticoids outlined above, corticosteroid treatment likely attenuates the COVID-19 induced inflammatory response – particularly in severely affected patients. Indeed, administration of glucocorticoids was reported to reduce CRP and IL-6 plasma levels in COVID-19 patients, without affecting virus clearance 58 59 . Future studies identifying glucocorticoid target cells and anti-inflammatory mechanisms in the context of COVID-19 are critical in order enable the development of targeted therapies in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the known and extensive immunosuppressive effects of glucocorticoids outlined above, corticosteroid treatment likely attenuates the COVID-19 induced inflammatory response – particularly in severely affected patients. Indeed, administration of glucocorticoids was reported to reduce CRP and IL-6 plasma levels in COVID-19 patients, without affecting virus clearance 58 59 . Future studies identifying glucocorticoid target cells and anti-inflammatory mechanisms in the context of COVID-19 are critical in order enable the development of targeted therapies in the future.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth nothing that in this study we define high dose corticosteroids pulses as doses of at least 125 mg of methylprednisolone or dexamethasone equivalent. Previous studies in COVID-19 patients did not found clinical differences between methylprednisolone doses above 125 mg [ 14 , 25 , 26 ]. We also tested for low corticosteroid doses and did not find a statistically significant difference in outcome.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have shown that corticosteroid therapy does not affect virus clearance time [ 38 ]. Unfortunately, in our study we did not carry out a follow up quantify viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the anti-inflammatory mechanisms, compound 12 in LH capsules can inhibit the inflammatory cytokine storm by inhibiting the phosphorylation of JAK1/2, which is downstream of IL-6( Billing et al, 2019 ). IL-6 can be used as a biomarker of the severity and prognosis related to cytokine storms( Del Valle et al, 2020 ; Guo et al, 2020 ; Liu et al, 2020a ), and its expression is higher than those of TNF-α and IL-1. High concentrations of IL-6 can induce various pathological functions related to thrombosis, vascular leakage and myocardial dysfunction, and these effects lead to tissue hypoxia, hypotension, multiple organ dysfunction, and diffuse intravascular coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is currently no vaccine or antiviral treatment for patients with suspected or confirmed COVID-19( Amin and Jha, 2020 ; Kouznetsov, 2020 ; Shang et al, 2020 ; Shi et al, 2020 ). The drugs that are clinically used include remdesivir, abidol, and RNA synthesis hormones( Chu et al, 2004 ; Liu et al, 2020a ; Lu, 2020 ; Zheng et al, 2020 ), but the efficacy and safety of these drugs still need further clinical confirmation. With respect to vaccines, 30 vaccine candidates have been reported to the WHO and are in the clinical phase, but only six vaccines have entered the III clinical phase as of August 20, 2020( Florindo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%